KEEFEKTIFAN MODEL TIME TOKEN ARENDS BERBANTU MEDIA ULTRAS TERHADAP HASIL BELAJAR IPA PADA SISWA KELAS V SD NEGERI 01 KARANGSONO GROBOGAN - Niken Wulandari (Jurnal Guru Kita PGSD, 2019)
Abstract: The Effectiveness of the Time Token Arends Model Assisted by Ultras Media on Science Learning Outcomes of Grade V Students of SD Negeri 01 Karangsono Grobogan. This study aims to determine the achievement of learning success by applying the Time Token Arends model assisted by Ultras media in fifth grade students of SD Negeri 01 Karangsono and to know the differences in the pre-test and post-test scores in the Natural Science subject of Respiratory materials by applying the Time Token Arends model. Ultras media in fifth grade students of SD Negeri 01 Karangsono. This type of research is quantitative research in the form of Pre-Experimental Design with the type of One Group Pretest-Posttest. The population of this research is the fifth grade students of SD Negeri 01 Karangsono 2017/2018. Samples taken were 20 students. Data in this study were obtained through tests, documentation, and interviews. The results showed that the posttest scores in class V SDN 01 Karangsono after using the Time Token Arends learning model were better than the pretest scores before using the Time Token Arends learning model.Keywords:Learning outcomes,Time Token Arends, Media  UltrasAbstrak: Keefektifan Model  Time Token Arends Berbantu Media  Ultras Terhadap Hasil Belajar  IPA Pada Siswa Kelas V SD Negeri 01 Karangsono Grobogan.Penelitian ini bertujuan untuk mengetahuipencapaian keberhasilan belajar pembelajaran dengan menerapkan model Time Token Arends berbantu media Ultras pada siswa kelas V SD Negeri 01 Karangsono dan mengetahui perbedaan nilai pre-test dan post-test pada pelajaran IPA materi Alat Pernapasan dengan menerapkan model Time Token Arends berbantu media Ultras pada siswa kelas V SD Negeri 01 Karangsono.Jenis penelitian ini adalah penelitian kuantitatif dalam bentuk Pre-Eksperimental Design dengan jenis One Group Pretest-Posttest.Populasi penelitian ini adalah siswa kelas V SD Negeri 01 Karangsono 2017/2018.Sampel yang diambil adalah 20 siswa.Data dalam penelitian ini diperoleh melalui tes, dokumentasi, dan wawancara.Hasil penelitian menunjukkan bahwa nilai posttest  pada kelas V SDN 01 Karangsono setelah menggunakan model pembelajaran Time Token Arends lebih baik dari nilai pretest sebelum menggunakan model pembelajaran Time Token Arends. Kata Kunci :Hasil Belajar, Time Token Arends, Media  Ultras